Stabilisation of the Lagos-Ibadan expressway’s Ojoo-Iwo Road section using geosynthetics (2024)
Road performance and longevity are greatly enhanced by geosynthetics. It carries out a number of functions, including reinforcement, stability, separation, fluid barrier, drainage, and filtration, to improve their use on road pavement. Geosynthetic materials were introduced to some sections of the subbase layer of the Lagos- Ibadan expressway to enhance the overall performance of the pavement. Soil samples were collected at a burrow pit at km 90 of the Lagos-Ibadan Expressway. The contractor handling the Ojoo-Iwo road segment of the expressway provided the geosynthetic materials employed in the study. The natural moisture content of the soil, sieve analysis, Atterberg limits, optimum moisture content, Maximum Dry Density (MDD), and California Bearing Ratio (CBR) were determined using standard procedures. The soil is gapped-graded, sandy-gravel, and has a plasticity index of 8%. The natural and stabilized soils have corresponding MDDs of 2040 and 1960 kg/m3. After the geosynthetic materials were added to the subbase layer, the soil sample’s CBR rose from 26% to 30%.